Talking about dying and death: a focus group study to explore a local community perspective - Marilyn N. Y. Kirshbaum; Ian carey; Brigid Purcell; Seamus Nash (MDPI AG, 2011)
There is a general perception held by health care practitioners based in hospices, palliative care services and general healthcare services that society is reluctant to talk about dying and death. This avoidance behaviour is observed, noted and expressed in national policy briefings as being detrimental to patient involvement in decision making, effective coping and preparation for death, organ donation, writing a will, and the process of bereavement. The aim of the pilot study was to explore the perceptions of a local community on the broad subject of Talking about Dying and Death. An interactive qualitative methodology using a constructivist approach enabled exploration of a wide range of views from a self-selected group resident within the local community (n=8). Data were collected from a focus group session facilitated by the researcher and an associate researcher. Systematic and analytical coding of transcripts was undertaken using Framework Analysis (Richie and Spencer 1994). Four overriding themes were identified: i) emotions, beliefs and behaviours; ii) coping with adversity; iii) difficulties, barriers and tensions, and iv) fostering a participative future. There were some notions of superstition amongst the participants, but little mention of formal religious beliefs. Within the themes, Coping with Adversity and Difficulties, Barriers and Tensions is the core of the community’s views and needs. The link to the local hospice service is significant for it is the place where practical help, spiritual care, and an appreciation for sensitivity, openness and honesty can be put into action. The importance of communication and language are critical above all else. Dying and death was articulated as an upsetting topic, and remains a taboo in this community in the United Kingdom, with a belief that talking will bring harm. Promotion of talking about dying and death was discussed in relation to the role of the local hospice and several suggestions were put forward.